Bledology - Charney, Noah (knjige, 2025)
Bledology is part travel guide, part travelogue, and part historical record. It is written by Dr Noah Cherney, an American author and professor in love with Slovenia who has been living here for more than a decade. Deliberately subjective, humorous, yet also practical, it is the only book you'll need about Bled—whether as a souvenir of your visit or as preparation for a holiday in what the author calls the most beautiful place on Earth.